Sedimentary tectonics of the East Rand Basin, with special reference to the Brakpan formation - Wagener, G. F.(Guillaume Francois) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1972.